Phytochemical Analysis and Antimicrobial Activity of Methanolic and Aqueous Stem Extracts of Guiera senegalensis Against Bacterial Pathogens - Tyohemba, Samuel Terhide; Suwaiba, Ladan Muhammad; Ndukwe, Nelson Nwachukwu; Adoyi, Michael Paul; Catherine O., Attah; Asiya, Mamoon; Mbahi, Asugu Mary (FUDMA Journal of Sciences, 2025)
With the growing resistance of pathogens to conventional antibiotics, there is an increasing interest in exploring alternative treatments derived from medicinal plants, particularly those rich in bioactive compounds. Guiera senegalensis, a medicinal shrub native to West and Central Africa, has traditionally been used to treat gastrointestinal disorders, fever, and rheumatism. This study aimed to investigate the presence of bioactive compounds and antimicrobial properties of the stem extract of G. senegalensis, with a particular focus on its efficacy against bacterial infections.Phytochemicals were extracted through cold maceration using methanol and distilled water as solvents. The antimicrobial effects of the extracts on clinical isolates of Salmonella typhi, Escherichia coli, and Pseudomonas aeruginosa were evaluated via the agar disc diffusion method.Phytochemical analysis of both the methanol and aqueous extracts revealed the presence of alkaloids, flavonoids, tannins, and saponins. The methanol extract exhibited higher concentrations of flavonoids, tannins, and saponins, whereas the aqueous extract contained more alkaloids. Antimicrobial assays demonstrated that both extracts inhibited all tested bacterial strains, with the methanol extract demonstrating significant efficacy against E. coli, with an inhibition zone of 25 mm at 500 µg/mL. The minimum inhibitory concentration (MIC) values ranged from 6.25 to 500 µg/mL, indicating that these extracts may serve as alternative treatments for infections, particularly those resistant to antibiotics.These findings substantiate the therapeutic potential of G. senegalensis as a source of antimicrobial agents, corroborating its traditional use in treating infectious diseases.